KONSEP PENDIDIKAN PROFETIK (MELACAK VISI KENABIAN DALAM PENDIDIKAN) - Arifuddin Arifuddin (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2019)
Prophetic education is an educational model inspired by the educational model exemplified by Muhammad. The learning model practiced by the Prophet aims to form productive human beings and can contribute to the birth of scientific life that does not stop at the level of mere knowledge but can also be realized in daily life. Prophet Muhammad SAW. always make good as the main agenda and mission in each person's actions. He also became a human model that always rejected all forms of munkar and became evidence of the moral highness of the Prophet Muhammad. Therefore, his actions are often imaged as the Qur'an. Prophetic education is Islamic education based on values of humanization, liberation, and transcendence. These three pillars should be the central theme of Islamic education. First, calling on the righteous (ta`muruna bi al-ma'ruf). This can be understood as the spirit of fighting for humanitarian values. Second, preventing all forms of disobedience (wa tanhauna ‘an al-munkar). This point can be understood as an effort to liberate from all forms of oppression (liberation). Third, believe in Allah (wa tu’minuna billah) which means the idea of transcendence. A concept of faith that removes all forms of worship of God besides Allah SWT.